Challenges of education scenarios in primary care in the light of the Previne Brasil neoselectivity - Karina Magrini Carneiro Mendes; Leonardo Carnut; Lucia Dias da Silva Guerra; Claudia Camilo (Universidade Estadual de Maringá, 2024)
Primary Health Care (PHC) is considered a privileged space for the inclusion of students in the Unified Health System (UHS), which is most desirable the pedagogical scenario for the health course graduate education profile. However, its new financing model induces a neoselectivity that may mischaracterize UHS principles in primary care. This study is a qualitative meta-synthesis to understand the challenges of teaching practice scenarios in PHC, identified in the research, in order to discuss them in light of the limits imposed by the neoselectivity, induced by the Previne Brasil Program (Prevent Brazil Program). A search was conducted on the Virtual Health Library (VHL) portal. The search strategy was designed using the following keywords: 'practice scenarios in higher education' (object), 'challenges' (qualifier) and 'PHC' (amplitude/limit). The selection of publications was carried out using the PRISMA protocol by two independent reviewers, and data analysis was performed in the thematic modality. The quality analysis of the articles was based on the CASP protocol and the internal validation of the excerpts was done by a third evaluator. From the 17 articles included in the review, it was possible to extract 5 analytical dimensions of the scenarios' challenges, which are related to: 'care', 'teaching', 'management', 'health professionals' attitude', 'community attitude'. All dimensions presented several sub-themes, except for 'community attitude'. Given the existing challenges, the neoselectivity induced in PHC tends to intensify most of the problems. It is assumed that the impacts on PHC settings may, in the future, place it as a non-viable practice scenario.